Study of collection potato varieties on productivity and disease resistance - N. F. Sintsova (Аграрная наука Евро-Северо-Востока, 2017)
Under conditions of east part of central zone of Kirov region study of economical valuable trait of potato collection nurcery accessions was conducted. For 2012…2016 group of 27 varieties was selected with high productivity exceeded standard Udacha by 103…130%. It was established that varietal productivity was in close relation with amount of precipitations in Yuly-August (r = 0.91). Variability of trait "productivity" within collection nurcery was an average 29.8%, within highly productive varieties - 42.7%. Highest coefficient of variation (55.7…55.9%) had varieties Isna, Arnica (Germany), Ibus (Poland), Рагнеда (Belarus). Stable high productivity at a level of 780…735 g/bush was in varieties Debryansk, 217-07, 21-07 (Russia), Zarevo (Ukraine) 23.8…29.3%. For this group of varieties the cluster analysis was conducted that allowed to unitу sample into groups of similar clusters. Highest distance shown genetic remoteness was in accessions Debryansk and 217-07 (Russia). These varieties could be used in crossings with all other varieties with high possibility of selection of transgressive forms. It was conducted additional cluster analysis on diseases resistance: to phytophtorosis - on leaves and tubers, to alterniosis, to scab, to viruses. Varieties Zarevo (Ukraine) and Zhukovsky ranny (Russia) were selected that shown strong divergence with other varieties by reaction on phytopathogenes. Because of devision of all sample into two clusters on productivity and three clusters on disease resistance optimal schemes of breeding were chosen for creation of new high-productive potato varieties for Volga-Vyatka region.